Supercondutividade de partículas confinadas em um modelo de teoria de campos - Santos, João Paulo Sampaio (2022)
Submitted by Teresa Silva CTC/D (teresadasilvarj@gmail.com) on 2022-01-18T12:00:45Z No. of bitstreams: 1 Dissertação - João Paulo Sampaio Santos - 2021 - Completa.pdf: 2353971 bytes, checksum: 2924b875285e6e92db8066c024dbc9c4 (MD5)